A secondary battery and an electronic device

CN118040086BActive Publication Date: 2026-10-09DONGGUAN AMPEREX TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410277253.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2026-10-09
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

[0003]目前将高强度薄膜化的聚烯烃多孔膜(即微孔膜),微孔膜是一种具有各向异性孔隙的高孔隙度薄膜,其孔径大小通常在0.1μm至1μm之间,作为锂离子电池隔膜,微孔膜通常由聚烯烃等材料通过湿法工艺或干法工艺采用单向拉伸或双向拉伸制备得到,但聚烯烃多孔膜中的聚烯烃玻璃化转变温度较低,当锂离子电池内部温度升高时,隔膜的膨胀收缩容易影响到锂离子电池的安全性能和循环寿命

Benefits of technology

[0018] This application provides a secondary battery including an electrode assembly comprising a positive electrode, a negative electrode, a first separator, and a second separator. The first separator is located between the positive and negative electrode, and the negative electrode is located between the first and second separators. The first separator includes a first base membrane, and the second separator includes a second base membrane. The first base membrane is a non-woven fabric membrane, and the second base membrane is a microporous membrane. The thickness of the non-woven fabric membrane is 10 μm to 15 μm, and the thickness of the microporous membrane is 5 μm to 9 μm. When the microporous membrane is used in conjunction with the non-woven fabric membrane, as the internal temperature of the secondary battery rises during charging and discharging, the separator can maintain a high porosity, allowing for smooth electrolyte flow and improving the lithium-ion transport rate. By controlling the thickness of the non-woven fabric membrane and the microporous membrane within the aforementioned ranges, both the non-woven fabric membrane and the microporous membrane possess good mechanical strength, enabling the secondary battery to achieve both high energy density and improved safety performance, thus extending cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118040086B_ABST
    Figure CN118040086B_ABST
Patent Text Reader

Abstract

The application provides a secondary battery and an electronic device. The secondary battery comprises an electrode assembly, the electrode assembly comprises a positive electrode sheet, a negative electrode sheet, a first separator and a second separator, the first separator is located between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet is located between the first separator and the second separator, the first separator comprises a first base film, and the second separator comprises a second base film. The first base film is a non-woven fabric film, and the second base film is a microporous film. The thickness of the non-woven fabric film is 10-15 mu m, and the thickness of the microporous film is 5-9 mu m. Through the above arrangement, the secondary battery obtained has long cycle life and good safety performance while having high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a secondary battery and electronic device. Background Technology

[0002] Compared with lead-acid batteries, lithium-ion batteries have advantages such as high energy density, long cycle life, low self-discharge rate, and environmental friendliness, and are widely used in aviation, aerospace, marine, and electric vehicle fields. The performance of the separator in a lithium-ion battery determines the interface structure and internal resistance, directly affecting the battery's capacity, cycle life, and safety performance. A high-performance separator plays a crucial role in improving the overall performance of the battery.

[0003] Currently, high-strength thin-film polyolefin porous membranes (i.e., microporous membranes) are being developed. Microporous membranes are highly porosimetric films with anisotropic pores, typically ranging from 0.1 μm to 1 μm in size. As lithium-ion battery separators, microporous membranes are usually prepared from polyolefins and other materials through wet or dry processes using uniaxial or biaxial stretching. However, the glass transition temperature of polyolefins in polyolefin porous membranes is relatively low. When the internal temperature of the lithium-ion battery rises, the expansion and contraction of the separator can easily affect the safety performance and cycle life of the lithium-ion battery. When using nonwoven fabric as the separator substrate, the higher glass transition temperature of the nonwoven fabric can reduce the above problems. However, the greater thickness of the nonwoven fabric can easily lead to a loss of energy density in the lithium-ion battery. Summary of the Invention

[0004] The purpose of this application is to provide a secondary battery and electronic device that, while maintaining energy density, improves the safety performance of the secondary battery and extends its cycle life.

[0005] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0006] The first aspect of this application provides a secondary battery, which includes an electrode assembly comprising a positive electrode, a negative electrode, a first separator, and a second separator. The first separator is located between the positive and negative electrode, and the negative electrode is located between the first and second separators. The first separator includes a first base membrane, and the second separator includes a second base membrane. The first base membrane is a non-woven fabric membrane, and the second base membrane is a microporous membrane. The thickness of the non-woven fabric membrane is 10 μm to 15 μm, and the thickness of the microporous membrane is 5 μm to 9 μm. When the microporous membrane is used in conjunction with the non-woven fabric membrane, as the internal temperature of the secondary battery rises during the charging and discharging process, the separator can maintain a high porosity, allowing for smooth electrolyte flow and improving the lithium-ion transport rate. By controlling the thickness of the non-woven fabric membrane and the microporous membrane within the aforementioned ranges, both the non-woven fabric membrane and the microporous membrane possess good mechanical strength, enabling the secondary battery to achieve both high energy density and improved safety performance, thus extending cycle life.

[0007] In one embodiment of this application, the electrode assembly is a wound structure. The negative electrode includes a negative current collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative current collector. Along the winding direction of the electrode assembly, the length of the first negative electrode material layer is greater than the length of the second negative electrode material layer. A first separator is located on one side of the first negative electrode material layer of the negative electrode, and a second separator is located on one side of the second negative electrode material layer of the negative electrode. When the electrode assembly is a wound structure, the nonwoven membrane has a larger porosity, which is beneficial for adsorbing more electrolyte. When the first separator is located on one side of the first negative electrode material layer of the negative electrode, it is beneficial for storing more electrolyte at the A-side of the negative electrode of the secondary battery, reducing the risk of lithium plating at the interface between the electrolyte and the negative electrode due to electrolyte bridging in the later stages of the secondary battery cycle. At the same time, the dual separator structure of microporous membrane and nonwoven membrane in the secondary battery, while taking into account energy density, is beneficial for improving the safety performance of the secondary battery and extending its cycle life. In this application, the A-side of the negative electrode sheet refers to one side of the negative electrode sheet that includes the first negative electrode material layer, that is, the side of the negative electrode material layer that is longer in the negative electrode sheet.

[0008] In one embodiment of this application, the first separator includes a first adhesive layer located on both sides of a first base film and a first ceramic coating disposed on the surface of the first base film near the positive electrode, the first ceramic coating being located between the first base film and the first adhesive layer; the second separator includes a second adhesive layer located on both sides of a second base film and a second ceramic coating disposed on the surface of the second base film away from the negative electrode, the second ceramic coating being located between the second base film and the second adhesive layer, the coating weight of the first adhesive layer being greater than the coating weight of the second adhesive layer. The placement of the first ceramic coating between the first base film and the first adhesive layer, and the placement of the second ceramic coating between the second base film and the first adhesive layer, is beneficial for improving the heat resistance and electrolyte affinity of both the first and second separators; the placement of the first adhesive layer on both surfaces of the first base film and the second adhesive layer on both surfaces of the second base film is beneficial for improving the adhesion between the first separator and the positive electrode, the adhesion between the first separator and the negative electrode, and the adhesion between the second separator and the negative electrode, thereby improving the cycle performance of the secondary battery. When the coating weight of the first adhesive layer is greater than that of the second adhesive layer, the adhesion between the first separator and the positive electrode, and between the first separator and the negative electrode, is stronger. Furthermore, when the electrode assembly has a wound structure, it is more conducive to improving the compressive stress at the corners of the electrochemical device. Therefore, the secondary battery, while maintaining energy density, also possesses a long cycle life and good safety performance.

[0009] In one embodiment of this application, the coating weight of the first adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 The coating weight of the second adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 By adjusting the coating weights of the first and second adhesive layers within the aforementioned ranges, higher adhesion is achieved between the first separator and the positive electrode, between the first separator and the negative electrode, and between the second separator and the negative electrode, thereby improving the cycle performance of the secondary battery. A larger coating weight of the first adhesive layer results in stronger adhesion between the first separator and the positive electrode, and between the first separator and the negative electrode. Consequently, the secondary battery achieves a longer cycle life and better safety performance while maintaining sufficient energy density.

[0010] In one embodiment of this application, the coating weight of the first ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2 The coating weight of the second ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2By adjusting the coating weight of the first ceramic layer and the coating weight of the second ceramic layer within the above-mentioned range, it is beneficial to improve the thermal stability and mechanical properties of the first and second separators, while also improving their liquid retention and wetting properties. As a result, the secondary battery has a long cycle life and good safety performance while maintaining energy density.

[0011] In one embodiment of this application, the first adhesive layer includes a first adhesive, and the second adhesive layer includes a second adhesive. The first and second adhesives are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, or polyimide. By selecting the aforementioned types of first and second adhesives, the adhesion between the first base film and the first adhesive layer, and between the second base film and the second adhesive layer, is improved, thereby enhancing the cycle performance of the secondary battery. Thus, the secondary battery achieves a long cycle life and good safety performance while maintaining sufficient energy density.

[0012] In one embodiment of this application, the porosity of the first base film is 40% to 70%, and the porosity of the second base film is 5% to 50%. By adjusting the porosity of the first base film and the porosity of the second base film within the above ranges, lithium ions exhibit better kinetic performance during the charging and discharging process of the secondary battery, and can adsorb more electrolyte, thereby improving the cycle performance of the secondary battery and extending its cycle life.

[0013] In one embodiment of this application, the material of the first base membrane includes at least one selected from polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyetheretherketone, polyphenylene sulfide, polyacrylate, polyethylene terephthalate, poly(p-phenyleneamide), polyarylether sulfone ketone, aramid, or aramid sulfone. The material of the second base membrane includes a polyolefin, wherein the polymerizing monomer of the polyolefin includes at least one selected from ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, cyclobutene, cyclopentene, or cyclohexene. When the materials of the first and second base membranes within the above range are selected, the double-membrane structure of the first and second separators in the secondary battery can improve the safety performance and extend the cycle life of the secondary battery while maintaining energy density.

[0014] In one embodiment of this application, the nonwoven membrane material includes polyethylene terephthalate, and the microporous membrane material includes at least one of polypropylene and polyethylene. When nonwoven membrane materials and microporous membrane materials within the above range are selected, a double-membrane structure including a microporous membrane and a nonwoven membrane is provided in the secondary battery. This approach balances energy density while improving the safety performance of the secondary battery and extending its cycle life.

[0015] In one embodiment of this application, the glass transition temperature of the nonwoven membrane is 80°C to 100°C, and the glass transition temperature of the microporous membrane is 25°C to 50°C. When the glass transition temperatures of the nonwoven membrane and the microporous membrane are within the above ranges, the provision of a double-membrane structure including a microporous membrane and a nonwoven membrane in the secondary battery can improve the safety performance and extend the cycle life of the secondary battery while maintaining energy density.

[0016] A second aspect of this application provides an electronic device comprising a secondary battery as described in any of the foregoing embodiments. The secondary battery provided by this application combines high energy density with long cycle life and good safety performance; therefore, the electronic device of this application has a long service life.

[0017] The beneficial effects of this application are:

[0018] This application provides a secondary battery including an electrode assembly comprising a positive electrode, a negative electrode, a first separator, and a second separator. The first separator is located between the positive and negative electrode, and the negative electrode is located between the first and second separators. The first separator includes a first base membrane, and the second separator includes a second base membrane. The first base membrane is a non-woven fabric membrane, and the second base membrane is a microporous membrane. The thickness of the non-woven fabric membrane is 10 μm to 15 μm, and the thickness of the microporous membrane is 5 μm to 9 μm. When the microporous membrane is used in conjunction with the non-woven fabric membrane, as the internal temperature of the secondary battery rises during charging and discharging, the separator can maintain a high porosity, allowing for smooth electrolyte flow and improving the lithium-ion transport rate. By controlling the thickness of the non-woven fabric membrane and the microporous membrane within the aforementioned ranges, both the non-woven fabric membrane and the microporous membrane possess good mechanical strength, enabling the secondary battery to achieve both high energy density and improved safety performance, thus extending cycle life.

[0019] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these drawings.

[0021] Figure 1 This is a schematic diagram of the electrode assembly structure according to one embodiment of this application;

[0022] Figure 2 This is a schematic diagram of the electrode assembly unfolded along the W direction according to another embodiment of this application;

[0023] Figure 3 for Figure 2 Schematic diagram of the wound structure formed by the electrode assembly;

[0024] Figure 4 for Figure 3 A magnified view of region Q in the electrode assembly.

[0025] Reference numerals: Electrode assembly 100; First separator 10; First base film 11; First adhesive layer 12; First ceramic coating 13; Second separator 20; Second base film 21; Second adhesive layer 22; Second ceramic coating 23; Negative electrode 30; Negative current collector 31; Negative electrode material layer 32; First negative electrode material layer 33; Second negative electrode material layer 34; Positive electrode 40; Positive current collector 41; Positive electrode material layer 42. Detailed Implementation

[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0027] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.

[0028] The first aspect of this application provides a secondary battery, such as Figure 1As shown, the secondary battery includes an electrode assembly 100, which includes a first separator 10, a second separator 20, a negative electrode 30, and a positive electrode 40. The first separator 10 is located between the positive electrode 40 and the negative electrode 30, and the negative electrode 30 is located between the first separator 10 and the second separator 20. The first separator 10 includes a first base membrane 11, and the second separator 20 includes a second base membrane 21. The first base membrane 11 is a non-woven fabric membrane, and the second base membrane 21 is a microporous membrane. The thickness H1 of the non-woven fabric membrane is 10 μm to 15 μm, and the thickness H2 of the microporous membrane is 5 μm to 9 μm. For example, the thickness H1 of a nonwoven membrane can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any combination of two of these values; the thickness H2 of a microporous membrane can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or any combination of two of these values. Microporous membranes are typically prepared from materials such as polyolefins using wet or dry processes with uniaxial or biaxial stretching, or by thermally induced phase separation. They are inexpensive, possess good mechanical strength and chemical stability, and exhibit good resistance to organic solvents. Furthermore, the thickness of microporous membranes is usually small, making them suitable for use in secondary batteries where, for the same battery volume, the volumetric energy density is higher. However, microporous membranes have a low glass transition temperature. During the charging and discharging process of a secondary battery, when the internal temperature reaches around 60°C, the expansion and contraction of the positive and negative electrode plates due to lithium ion insertion and extraction generate internal stress. This internal stress is transferred to the microporous membrane, causing it to be compressed and its porosity to gradually decrease. Lower porosity makes lithium ion insertion and extraction difficult, shortening the cycle life of the secondary battery. Furthermore, reduced porosity makes it difficult for heat to dissipate from the battery, leading to excessive temperature rise and reduced safety performance. Nonwoven membranes, on the other hand, have better electrolyte storage performance and a higher glass transition temperature, resulting in better thermal stability. As the internal temperature rises during charging and discharging, the nonwoven membrane maintains high porosity while possessing high mechanical strength, allowing for smooth electrolyte flow and improving lithium ion transport rate. However, nonwoven membranes are typically thicker, which can lead to a loss of energy density in the secondary battery. When the thickness of the nonwoven membrane and the microporous membrane is too small, i.e., less than the lower limit of the scope of this application, lithium dendrites generated during the secondary battery cycle can easily pierce the microporous membrane with low strength, causing a short circuit and resulting in a decrease in the cycle performance of the secondary battery. When the thickness of the nonwoven membrane and the microporous membrane is too large, i.e., greater than the upper limit of the scope of this application, the lithium ion transport path is too long during the secondary battery cycle, resulting in a deterioration in the kinetic performance of the secondary battery and a decrease in the cycle performance of the secondary battery.When a microporous membrane is used in conjunction with a nonwoven membrane, and the thicknesses of both the nonwoven membrane and the microporous membrane are controlled within the scope of this application, both exhibit good mechanical strength. While maintaining energy density, this improves the safety performance of the secondary battery and extends its cycle life. In this application, it is understood that the thickness H1 of the nonwoven membrane is the thickness H1 of the first base membrane, and the thickness H2 of the microporous membrane is the thickness H2 of the second base membrane. This application does not impose any particular limitation on the method of controlling the thickness of the nonwoven membrane and the microporous membrane, as long as the purpose of this application is achieved. For example, commercially available nonwoven membranes and microporous membranes of different thicknesses can be selected, and the thicknesses of the nonwoven membrane and microporous membrane can be determined by combining the test method for "thickness test of the first base membrane and the second base membrane" in this application, thus selecting the desired thickness of the nonwoven membrane and microporous membrane.

[0029] In one embodiment of this application, the electrode assembly has a wound structure, such as... Figure 2 and Figure 3 As shown, the negative electrode 30 includes a negative current collector 31 and a first negative electrode material layer 33 and a second negative electrode material layer 34 located on both sides of the negative current collector 31. Along the winding direction W of the electrode assembly 100, the length of both ends of the first negative electrode material layer 33 is greater than the length of both ends of the second negative electrode material layer 34. The first separator 10 is located on one side of the first negative electrode material layer 33 of the negative electrode 30, and the second separator 20 is located on one side of the second negative electrode material layer 34 of the negative electrode 30. When the electrode assembly is a wound structure, the above arrangement, as shown... Figure 3 and Figure 4 As shown, the high porosity of the non-woven membrane is beneficial for storing more electrolyte. When the first separator is located on one side of the first negative electrode material layer of the negative electrode sheet, it facilitates the adsorption of more electrolyte at the A-side of the negative electrode sheet in the secondary battery, reducing the risk of lithium plating at the interface between the electrolyte and the negative electrode sheet due to electrolyte bridging in the later stages of the secondary battery cycle. Simultaneously, the dual-separator structure of microporous membrane and non-woven membrane in the secondary battery, while maintaining energy density, helps improve the safety performance of the secondary battery and extend its cycle life. In this application, the A-side of the negative electrode sheet refers to the side of the negative electrode sheet including the first negative electrode material layer, i.e., the side with the longer negative electrode material layer in the negative electrode sheet.

[0030] In one embodiment of this application, the electrode assembly is a wound structure. The negative electrode sheet includes a negative current collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative current collector. Along the winding direction of the electrode assembly, one end of the first negative electrode material layer and the second negative electrode material layer are flush, and the length of the other end of the first negative electrode material layer is greater than the length of the other end of the second negative electrode material layer. A first separator is located on one side of the first negative electrode material layer of the negative electrode sheet, and a second separator is located on one side of the second negative electrode material layer of the negative electrode sheet. When the electrode assembly is a wound structure, the nonwoven membrane has a high porosity, which is beneficial for adsorbing more electrolyte. When the first separator is located on one side of the first negative electrode material layer of the negative electrode sheet, it is beneficial for storing more electrolyte at the A-side of the negative electrode sheet of the secondary battery, reducing the risk of lithium plating at the interface between the electrolyte and the negative electrode sheet due to electrolyte bridging in the later stages of the secondary battery cycle. At the same time, the dual separator structure of microporous membrane and nonwoven membrane in the secondary battery, while taking into account energy density, is beneficial for improving the safety performance of the secondary battery and extending its cycle life.

[0031] In one embodiment of this application, the electrode assembly has a wound structure, such as... Figure 1 As shown, the negative electrode 30 includes a negative electrode current collector 31 and negative electrode material layers 32 located on both sides of the negative electrode current collector 31. Along the winding direction W of the electrode assembly 100, the lengths of the negative electrode material layers 32 on both sides of the negative electrode current collector 31 are equal. When the electrode assembly is a wound structure, this arrangement, while maintaining energy density, helps improve the safety performance of the secondary battery and increases its cycle life.

[0032] In one embodiment of this application, such as Figure 1 and Figure 2As shown, the first separator 10 includes a first adhesive layer 12 located on both sides of the first base film 11 and a first ceramic coating 13 disposed on the surface of the first base film 11 near the positive electrode 40, with the first ceramic coating 13 located between the first base film 11 and the first adhesive layer 12; the second separator 20 includes a second adhesive layer 22 located on both sides of the second base film 21 and a second ceramic coating 23 disposed on the surface of the second base film 21 away from the negative electrode 30, with the second ceramic coating 23 located between the second base film 21 and the second adhesive layer 22, and the coating weight of the first adhesive layer 12 is greater than the coating weight of the second adhesive layer 22. A first ceramic coating is disposed between the first base film and the first adhesive layer, and a second ceramic coating is disposed between the second base film and the first adhesive layer. This improves the heat resistance and electrolyte affinity of both the first and second separators. The first adhesive layer is disposed on both surfaces of the first base film, and the second adhesive layer is disposed on both surfaces of the second base film. This improves the adhesion between the first separator and the positive electrode, and between the first separator and the negative electrode, as well as the adhesion between the second separator and the negative electrode. It strengthens the interface between the separator and the positive and negative electrodes, facilitating lithium-ion transport and reducing the likelihood of the first and second ceramic coatings detaching, thereby improving the cycle performance of the secondary battery. When the coating weight of the first adhesive layer is greater than that of the second adhesive layer, the adhesion between the first separator and the positive and negative electrodes is stronger. Furthermore, when the electrode assembly has a wound structure, it further improves the stress distribution at the corners of the electrochemical device, reducing the risk of electrolyte bridging at these corners. Therefore, secondary batteries can balance energy density with long cycle life and good safety performance.

[0033] In one embodiment of this application, the coating weight CW1 of the first adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 The coating weight CW2 of the second adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 For example, the coating weight CW1 of the first adhesive layer can be 0.0004 mg / mm². 2 0.0008 mg / mm 2 0.001 mg / mm 2 0.0012 mg / mm 2 0.0015 mg / mm 2 0.0018 mg / mm 2 0.002 mg / mm 2 Or it can be a range consisting of any two of these values, and the coating weight CW2 of the second adhesive layer can be 0.0004 mg / mm². 20.0008 mg / mm 2 0.001 mg / mm 2 0.0012 mg / mm 2 0.0015 mg / mm 2 0.0018 mg / mm 2 0.002 mg / mm 2 This can be a range consisting of any two of these values. By adjusting the coating weights of the first and second adhesive layers within the aforementioned ranges, higher adhesion is achieved between the first separator and the positive electrode, between the first separator and the negative electrode, and between the second separator and the negative electrode. This strengthens the interfaces between the first separator and the positive electrode, between the first separator and the negative electrode, and between the second separator and the negative electrode, which is beneficial for lithium-ion transport. Simultaneously, it reduces the likelihood of the first and second ceramic coatings detaching, thereby improving the cycle performance of the secondary battery. A larger coating weight of the first adhesive layer results in stronger adhesion between the first separator and the positive electrode, and between the first separator and the negative electrode. Furthermore, when the electrode assembly has a wound structure, it is more conducive to improving the compression stress at the corners of the electrochemical device, reducing the risk of electrolyte bridging at these corners. Therefore, the secondary battery achieves a balance between energy density and long cycle life with good safety performance. In this application, the coating weight of the first adhesive layer and the coating weight of the second adhesive layer can be controlled by means known to those skilled in the art. For example, when coating the first adhesive layer slurry onto the surface of the first base film, the coating amount of the first adhesive layer slurry can be increased to increase the coating weight of the first adhesive layer, based on a certain solid content of the first adhesive layer slurry; when coating the second adhesive layer slurry onto the surface of the second base film, the coating amount of the second adhesive layer slurry can be increased to increase the coating weight of the second adhesive layer, based on a certain solid content of the second adhesive layer slurry. This application does not impose any particular restrictions, as long as the purpose of this application can be achieved.

[0034] In one embodiment of this application, the coating weight CW3 of the first ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2 The coating weight (CW4) of the second ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2 For example, the coating weight CW3 of the first ceramic coating can be 7 mg / cm³. 2 8mg / cm 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 13mg / cm 2Or, it can be a range consisting of any two of these values; the coating weight CW4 of the second ceramic coating can be 7 mg / cm³. 2 8mg / cm 2 9mg / cm 2 10mg / cm 2 11mg / cm 2 12mg / cm 2 13mg / cm 2 This can be a range consisting of any two of these values. By adjusting the coating weights of the first and second ceramic coatings within the aforementioned range, it is beneficial to improve the thermal stability and strength of the first and second separators, enhance their mechanical properties, reduce the possibility of large-area contact between the positive and negative electrode plates due to the shrinkage of the first and / or second separators during the charging and discharging of the secondary battery, and improve the binding capacity of the first and second separators, thereby improving the safety performance of the secondary battery. Simultaneously, the first and second ceramic coatings can absorb some electrolyte. Adjusting the coating weights of the first and second ceramic layers within the aforementioned range is beneficial to increase the liquid retention capacity of the first and second separators, thereby improving their liquid retention and wettability. Therefore, the secondary battery, while maintaining energy density, possesses a longer cycle life and better safety performance. In this application, the coating weight of the first ceramic coating and the coating weight of the second ceramic coating can be controlled by means known to those skilled in the art. For example, when coating the first ceramic coating slurry onto the surface of the first base film, the coating amount of the first ceramic coating slurry can be increased to increase the coating weight of the first ceramic coating, based on a certain solid content of the first ceramic coating slurry; when coating the second ceramic coating slurry onto the surface of the second base film, the coating amount of the second ceramic coating slurry can be increased to increase the coating weight of the second ceramic coating, based on a certain solid content of the second ceramic coating slurry. This application does not impose any particular restrictions, as long as the purpose of this application can be achieved.

[0035] In one embodiment of this application, the first adhesive layer includes a first adhesive, and the second adhesive layer includes a second adhesive. The first and second adhesives are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, or polyimide. By selecting the aforementioned first and second adhesives, the adhesion between the first base film and the first adhesive layer, and between the second base film and the second adhesive layer, is improved. This also enhances the adhesion between the first separator and the positive electrode, between the first separator and the negative electrode, and between the second separator and the negative electrode. Furthermore, it strengthens the interfaces between the first separator and the positive electrode, between the first separator and the negative electrode, and between the second separator and the negative electrode, facilitating lithium-ion transport and reducing the likelihood of the first and second ceramic coatings detaching, thereby improving the cycle performance of the secondary battery. Thus, the secondary battery achieves both high energy density and long cycle life with good safety performance. This application does not impose any particular limitation on the weight-average molecular weight of the first and second adhesives, as long as the objectives of this application are achieved. For example, the weight-average molecular weight of the first and second adhesives can be 1.5 × 10⁻⁶. 4 Up to 9×10 6 .

[0036] In one embodiment of this application, the porosity P1 of the first base membrane is 40% to 70%, and the porosity P2 of the second base membrane is 5% to 50%. For example, the porosity P1 of the first base membrane can be 40%, 43%, 45%, 47%, 50%, 53%, 55%, 57%, 60%, 63%, 65%, 67%, 70%, or any combination of two of these values, and the porosity P2 of the second base membrane can be 5%, 7%, 10%, 13%, 15%, 17%, 20%, 23%, 25%, 27%, 30%, 33%, 35%, 37%, 40%, 43%, 45%, 47%, 50%, or any combination of two of these values. By controlling the porosity of the first and second base membranes within the above ranges, the strength of the first and second separators is higher, thus improving the safety performance of the secondary battery. Lithium ions exhibit good kinetic performance during the charge-discharge transport process of secondary batteries and can adsorb a large amount of electrolyte. The good wetting properties of the first and second separators are beneficial for lithium ion transport, thereby improving the cycle performance and extending the cycle life of the secondary battery. This application does not impose any particular restrictions on the method of controlling the porosity of the first and second base films, as long as the purpose of this application can be achieved. For example, commercially available nonwoven membranes and microporous membranes with different porosities can be selected, and the porosities of the first and second base films can be determined by combining the test method of "porosity test of the first and second base films" in this application, thus selecting the nonwoven membrane and microporous membrane with the desired porosity.

[0037] In one embodiment of this application, the material of the first base film includes at least one selected from polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyetheretherketone, polyphenylene sulfide, polyacrylate, polyethylene terephthalate (PET), poly(p-phenyleneamide), polyarylether sulfone ketone, aramid, or aramid sulfone. The material of the second base film includes a polyolefin, wherein the polymerizing monomer of the polyolefin includes at least one selected from ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, cyclobutene, cyclopentene, or cyclohexene. For example, the material of the second base film may include at least one selected from polyethylene, polypropylene, poly-1-butene, poly-1-pentene, poly-1-hexene, poly-1-octene, poly-4-methyl-1-pentene, polycyclobutene, polycyclopentene, polycyclohexene, or ethylene-propylene copolymer. When the materials for the first and second base films within the aforementioned range are selected, a dual-membrane structure of the first and second separators in the secondary battery can improve the safety performance and cycle life of the secondary battery while maintaining energy density. This application does not impose any particular limitation on the weight-average molecular weight of the material of the first base film, as long as it achieves the purpose of this application. For example, the weight-average molecular weight of the material of the first base film can be 2 × 10⁻⁶. 5 Up to 1.5×10 6 This application does not impose any particular limitation on the weight-average molecular weight of the material of the second base film, as long as it can achieve the purpose of this application. For example, the weight-average molecular weight of the material of the second base film can be 2 × 10⁻⁶. 5 Up to 1.5×10 6 .

[0038] In one embodiment of this application, the nonwoven membrane material includes polyethylene terephthalate, and the microporous membrane material includes at least one of polypropylene (PP) and polyethylene (PE). When nonwoven membrane materials and microporous membrane materials within the above range are selected, a double-membrane structure including a microporous membrane and a nonwoven membrane is provided in the secondary battery. This approach balances energy density while improving the safety performance and cycle life of the secondary battery. This application does not impose any particular limitation on the preparation method of the microporous membrane, as long as it achieves the purpose of this application. For example, the microporous membrane can be prepared from the materials within the scope of this application by uniaxial or biaxial stretching using wet or dry processes, or by thermally induced phase separation. This application does not impose any particular limitation on the preparation method of the nonwoven membrane, as long as it achieves the purpose of this application. For example, the nonwoven membrane can be prepared from the materials within the scope of this application by at least one of meltblowing, spunbonding, wet papermaking, hydroentangling, needle punching, or hot rolling. In this application, it is understood that the material of the nonwoven membrane is the same as the material of the first base membrane, and the material of the microporous membrane is the same as the material of the second base membrane. Alternatively, commercially available nonwoven membranes and microporous membranes with different materials can be selected, along with the desired materials for the first and second base membranes. This application has no particular limitations, as long as the purpose of this application is achieved.

[0039] In one embodiment of this application, the glass transition temperature Tg1 of the nonwoven membrane is 80°C to 100°C, and the glass transition temperature Tg2 of the microporous membrane is 25°C to 50°C. For example, the glass transition temperature Tg1 of the nonwoven membrane can be 80°C, 83°C, 85°C, 87°C, 90°C, 92°C, 95°C, 97°C, 100°C, or any combination of two of these values; the glass transition temperature Tg2 of the microporous membrane can be 25°C, 27°C, 30°C, 32°C, 35°C, 37°C, 40°C, 42°C, 45°C, 47°C, 50°C, or any combination of two of these values. When the glass transition temperatures of the nonwoven membrane and the microporous membrane are within the above ranges, setting a double-membrane structure including a microporous membrane and a nonwoven membrane in the secondary battery can improve the safety performance and cycle life of the secondary battery while maintaining energy density. This application does not impose any particular restrictions on the method of controlling the glass transition temperature of the nonwoven membrane and the glass transition temperature of the microporous membrane, as long as the purpose of this application can be achieved. For example, it can be controlled by selecting different types of nonwoven membranes and microporous membranes. In this application, it is understood that the glass transition temperature Tg1 of the nonwoven membrane is the same as the glass transition temperature Tg1 of the first base membrane, and the glass transition temperature Tg2 of the microporous membrane is the same as the glass transition temperature Tg2 of the second base membrane.

[0040] In one embodiment of this application, the first ceramic coating comprises first ceramic particles, and the second ceramic coating comprises second ceramic particles. The first and second ceramic particles are each independently selected from at least one of alumina, boehmite, titanium dioxide, silicon dioxide, zirconium dioxide, tin dioxide, magnesium hydroxide, magnesium oxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, or silicon nitride. By selecting ceramic particles of the above types, the first and second ceramic coatings can possess high hardness and good heat resistance.

[0041] In one embodiment of this application, the first ceramic coating comprises first ceramic particles and a first ceramic coating adhesive, and the second ceramic coating comprises second ceramic particles and a second ceramic coating adhesive. This application does not impose any particular limitation on the types of the first and second ceramic coating adhesives, as long as the purpose of this application can be achieved. For example, the first and second ceramic coating adhesives are each independently selected from at least one of styrene-butadiene rubber, polyvinyl alcohol, polyvinylidene fluoride, polyacrylic acid, polymethyl methacrylate, polybutyl acrylate, or polyacrylonitrile. This application does not impose any particular limitation on the content of the first ceramic particles and the first ceramic coating adhesive in the first ceramic coating, or the content of the second ceramic particles and the second ceramic coating adhesive in the second ceramic coating, as long as the purpose of this application can be achieved. For example, based on the mass of the first ceramic coating, the mass percentage of the first ceramic particles is 5% to 95%, and the mass percentage of the first ceramic coating adhesive is 5% to 95%; based on the mass of the second ceramic coating, the mass percentage of the second ceramic particles is 5% to 95%, and the mass percentage of the second ceramic coating adhesive is 5% to 95%.

[0042] In one embodiment of this application, the first adhesive layer may further include a first thickener, and the second adhesive layer may further include a second thickener. Based on the mass of the first adhesive layer, the mass percentage of the first thickener is 0.3% to 6%. Based on the mass of the second adhesive layer, the mass percentage of the second thickener is 0.3% to 6%. Applying the first thickener to the first adhesive layer and the second thickener to the second adhesive layer helps to increase the stability of the first and second adhesive layer slurries and prevents sedimentation of the components in the first and second adhesive layer slurries. This application does not particularly limit the types of the first and second thickeners, as long as they can achieve the purpose of this application. For example, the first and second thickeners are each independently selected from at least one of hydroxyethyl cellulose, methyl hydroxyethyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, or sodium alginate.

[0043] The application has no particular limitation on the preparation method of the first separator, as long as the objective of the application can be achieved. For example, the preparation method of the first separator includes but is not limited to the following steps: (1) uniformly mixing a first binder and a first thickener to obtain a first adhesive layer slurry; (2) uniformly mixing first ceramic particles and a first ceramic coating binder to obtain a first ceramic coating slurry; (3) coating the first adhesive layer slurry on one surface of a first base film, and after drying, forming a first adhesive layer on one surface of the first base film; coating the first ceramic coating slurry on the other surface of the first base film, and after drying, forming a first ceramic coating on the other surface of the first base film; coating the first adhesive layer slurry on the surface of the first ceramic coating away from the first base film, and after drying, forming a first adhesive layer on the surface of the first ceramic coating away from the first base film, thus obtaining the first separator.

[0044] The application has no particular limitation on the preparation method of the second separator, as long as the objective of the application can be achieved. For example, the preparation method of the second separator includes but is not limited to the following steps: (1) uniformly mixing a second binder and a second thickener to obtain a second adhesive layer slurry; (2) uniformly mixing second ceramic particles and a second ceramic coating binder to obtain a second ceramic coating slurry; (3) coating the second adhesive layer slurry on one surface of a second base film, and after drying, forming a second adhesive layer on one surface of the second base film; coating the second ceramic coating slurry on the other surface of the second base film, and after drying, forming a second ceramic coating on the other surface of the second base film; coating the second adhesive layer slurry on the surface of the second ceramic coating away from the second base film, and after drying, forming a second adhesive layer on the surface of the second adhesive layer away from the second base film, thus obtaining the second separator.

[0045] The application has no particular limitation on the negative electrode current collector, as long as the objective of the application can be achieved. For example, the negative electrode current collector may comprise copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector (for example, a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.), etc. The negative electrode material layer or the first negative electrode material layer and the second negative electrode material layer of the present application comprise a negative electrode active material. The application has no particular limitation on the type of the negative electrode active material, as long as the objective of the application can be achieved. For example, the negative electrode active material may comprise natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, a silicon-carbon composite, SiO x (0<x<2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate Li4Ti5O with spinel structure 12The negative electrode material is selected from at least one of Li-Al alloy or metallic lithium. In this application, there are no particular limitations on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of this application is achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm, the thickness of the single-sided negative electrode material layer is 30 μm to 130 μm, the thickness of the first negative electrode material layer is 30 μm to 130 μm, and the thickness of the second negative electrode material layer is 30 μm to 130 μm. Optionally, the negative electrode material layer, the first negative electrode material layer, and the second negative electrode material layer may further include a conductive agent and a negative electrode binder. This application does not particularly limit the type of conductive agent in the negative electrode material layer, the first negative electrode material layer, and the second negative electrode material layer, as long as the purpose of this application is achieved. For example, the conductive agent may include, but is not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metallic materials, or conductive polymers. The aforementioned carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The aforementioned carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or carbon nanofibers. The aforementioned metallic materials may include, but are not limited to, metal powders and / or metal fibers; specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The aforementioned conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. This application does not impose any particular limitation on the type of negative electrode binder in the negative electrode material layer, the first negative electrode material layer, and the second negative electrode material layer, as long as it achieves the purpose of this application. For example, the negative electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene. This application does not impose any particular limitation on the mass ratio of the negative electrode active material, conductive agent, and negative electrode binder in the negative electrode material layer, the first negative electrode material layer, and the second negative electrode material layer, as long as it achieves the purpose of this application.

[0046] This application does not impose any particular limitation on the positive electrode sheet, as long as the purpose of this application can be achieved. In one embodiment of this application, when the electrode assembly is a wound structure, the positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The aforementioned "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its own thickness direction, or it can be disposed on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the positive current collector, or it can be a partial area of ​​the surface of the positive current collector; this application does not impose any particular limitation, as long as the purpose of this application can be achieved. For example, as shown... Figure 1 and Figure 2As shown, the positive electrode 40 includes a positive current collector 41 and a positive electrode material layer 42 disposed on both surfaces of the positive current collector 41. This application does not impose any particular limitation on the positive current collector, as long as it achieves the purpose of this application. For example, the positive current collector may include aluminum foil, aluminum alloy foil, or a composite current collector (e.g., an aluminum-carbon composite current collector). The positive electrode material layer of this application includes a positive electrode active material. This application does not impose any particular limitation on the type of positive electrode active material, as long as it achieves the purpose of this application. For example, the positive electrode active material may include at least one of lithium nickel cobalt manganese oxide (NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate. In this application, the positive electrode active material may also include non-metallic elements, such as at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur. In this application, there are no particular limitations on the thickness of the positive current collector and the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive current collector is 9 μm to 15 μm. The thickness of the single-sided positive electrode material layer is 30 μm to 120 μm. In this application, the positive electrode material layer may also include a conductive agent and a positive electrode binder. This application does not particularly limit the type of binder in the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the positive electrode binder can be the same type as the negative electrode binder in the aforementioned negative electrode material layer, first negative electrode material layer, and second negative electrode material layer. This application does not particularly limit the type of conductive agent in the positive electrode material layer, as long as the purpose of this application can be achieved. The conductive agent can be the same type as the conductive agent in the aforementioned negative electrode material layer, first negative electrode material layer, and second negative electrode material layer. This application does not particularly limit the mass ratio of the positive electrode active material, conductive agent, and positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of this application can be achieved.

[0047] The secondary battery in this application includes an electrolyte, which comprises a lithium salt and a non-aqueous solvent. The lithium salt may include at least one of LiPF6, LiNO3, LiBF4, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), or lithium difluoroborate. This application does not limit the content of the lithium salt in the electrolyte, as long as it achieves the purpose of this application. This application does not particularly limit the non-aqueous solvent, as long as it achieves the purpose of this application. For example, the non-aqueous solvent may include, but is not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents. The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, or methyl ethyl carbonate. The aforementioned cyclic carbonates may include, but are not limited to, at least one of ethylene carbonate, propylene carbonate (PC), butylene carbonate, or vinylene carbonate. Fluorinated carbonate compounds may include, but are not limited to, at least one of fluoroethylene carbonate, 1,2-difluoroethylene carbonate, 1,1,2-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. The aforementioned other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate.

[0048] The secondary battery of this application also includes a packaging bag for containing the positive electrode, negative electrode, separator, and electrolyte, as well as other components known in the art for secondary batteries. This application does not limit the aforementioned other components. This application does not impose any particular limitation on the packaging bag; it can be any packaging bag known in the art, as long as it can achieve the purpose of this application.

[0049] The secondary battery described in this application is not particularly limited and may include any device in which an electrochemical reaction occurs. In one embodiment of this application, the secondary battery may include, but is not limited to, a lithium-ion secondary battery, a lithium polymer secondary battery, or a lithium-ion polymer secondary battery.

[0050] This application does not impose any particular limitation on the preparation method of the secondary battery. Any preparation method known in the art can be used, as long as it can achieve the purpose of this application. For example, the preparation method of the secondary battery includes, but is not limited to, the following steps: stacking the positive electrode, the first separator, the negative electrode, and the second separator in sequence, and winding and folding them as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain the secondary battery.

[0051] A second aspect of this application provides an electronic device comprising a secondary battery as described in any of the foregoing embodiments. The secondary battery provided by this application combines high energy density with long cycle life and good safety performance; therefore, the electronic device of this application has a long service life.

[0052] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, household large-capacity batteries, and lithium-ion capacitors.

[0053] Example

[0054] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below.

[0055] Test methods and equipment:

[0056] Sampling methods for the first and second base membranes:

[0057] The lithium-ion batteries in the tested examples and comparative examples were disassembled, and the first and second separators were removed. They were soaked in dimethyl carbonate (DMC) for 20 minutes to remove electrolyte residue. Then, the first and second separators were placed in an oven and dried at 60°C for 12 hours to obtain first and second separator samples. The first and second separator samples obtained after cleaning and drying with DMC were placed in a container, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The container was then placed in an ultrasonic instrument with heating function for ultrasonication at 45°C for 3 hours. When the first and second separators became completely transparent, they were removed to obtain the first and second base film samples. The first and second base films were sampled using the above method for the following tests on porosity, thickness, and glass transition temperature of the first and second base films.

[0058] Porosity testing of the first and second base films:

[0059] The gas displacement method is used for testing. The first and second base film samples are prepared by punching with a mold (those skilled in the art can select molds of common sizes and shapes in the art according to the size, shape, and testing equipment requirements of the test samples). The true volume V0 of the sample is measured by a true density tester. The apparent volume V of the sample can be calculated from the area and thickness of the sample. Then, the percentage of the sample pore volume to the total area P = (V-V0) / V×100%, which is the porosity of the first or second base film.

[0060] Thickness testing of the first and second base films:

[0061] The first base film sample underwent washing, drying, cutting, and polishing to obtain a cross-sectional scanning electron microscope (SEM) test sample of the first base film. The morphology of the cross-section of the first base film along the thickness direction was observed and SEM images were taken using a field emission scanning electron microscope (Philips XL-30). The thickness of the first base film, i.e., the thickness H1 of the nonwoven film, was measured using the SEM.

[0062] The second base film sample underwent washing, drying, cutting, and polishing to obtain a cross-sectional scanning electron microscope (SEM) test sample of the second base film. The morphology of the cross-section of the second base film along the thickness direction was observed and SEM images were taken using a field emission scanning electron microscope (Philips XL-30). The thickness of the second base film, i.e., the thickness H2 of the microporous membrane, was measured using the SEM.

[0063] Glass transition temperature tests of the first and second base films:

[0064] The glass transition temperatures of the nonwoven membrane (first base film sample) and the microporous membrane (second base film sample) were tested using differential scanning calorimetry (DSC). The first and second base film samples were prepared by punching and cutting using a mold (those skilled in the art can select molds of common sizes and shapes according to the size and shape of the test sample and the requirements of the testing equipment). The prepared samples were sealed in self-sealing bags to avoid contamination. During testing, the samples were removed and placed in a crucible, which was then placed in a furnace. The temperature was increased from -100℃ to 800℃ at a rate of 5℃ / min. The temperature change was controlled by a program. Simultaneously, the power difference (heat flow rate) between the sample and the reference material was measured with respect to temperature, thereby obtaining information such as the melting point, crystallinity, and crystallization temperature of the test samples. The glass transition temperatures of the test samples, namely the glass transition temperature Tg1 of the nonwoven membrane and the glass transition temperature Tg2 of the microporous membrane, were obtained through DSC curves.

[0065] Lithium-ion battery thickness testing:

[0066] Adjust the test pressure to the required 600g by adding or removing weights; place a 3mm gauge block on the platform, press the white buttons on both sides, and the panel pressure gap battery thickness gauge (PPG battery thickness gauge) will automatically feed the gauge block in and test it. Test any 9 points in sequence, and verify the tolerance to ±0.02mm. It can only be used if it is within the specification; hold the lithium-ion battery with one hand, barcode side up, on the platform, scan the barcode first, and then press the white buttons on both sides. The instrument will automatically feed the lithium-ion battery in and test it. Record the test result, which is the thickness of the lithium-ion battery.

[0067] The thickness of a lithium-ion battery characterizes its energy density; for the same volume, a greater thickness indicates a lower energy density.

[0068] Cyclic performance test:

[0069] At 25°C, the lithium-ion battery was charged at a constant current of 2C to 4.5V, then charged at a constant voltage of 4.5V to a current of 0.02C. After resting for 5 minutes, it was discharged at a constant current of 0.7C to 3.0V. This was the first cycle, and the discharge capacity was recorded. The lithium-ion battery was subjected to charge-discharge cycles according to the above process. The test was stopped after 1000 cycles (cls), and the capacity retention rate was calculated as an indicator to evaluate the cycle performance of the lithium-ion battery.

[0070] Capacity retention rate (%) = (Discharge capacity after 1000 cls of cycling / Discharge capacity of the first cycle) × 100%.

[0071] Hot box test:

[0072] Under conditions of 25℃, lithium-ion batteries that have been charged at a constant current of 2C to 4.5V and then at a constant voltage of 4.5V to a current of 0.02C are placed in a test chamber with circulating air convection, a temperature of 25℃, and a humidity of 80%. After standing for 5 minutes, the test chamber is heated to 130℃ at a rate of 5℃ / min and maintained at 130℃ for 10 minutes. The test is then stopped, and the lithium-ion batteries are checked for fire or explosion. A battery that does not fire or explode is considered to have passed the test. The pass rate for the 130℃ hot chamber test is calculated as: (Number of batteries passing the 130℃ hot chamber test) / (Total number of batteries tested at 130℃, 5 batteries).

[0073] Under conditions of 25℃, lithium-ion batteries that have been charged at a constant current of 2C to 4.5V and then at a constant voltage of 4.5V to a current of 0.02C are placed in a test chamber with circulating air convection, a temperature of 25℃, and a humidity of 80%. After standing for 5 minutes, the test chamber is heated to 135℃ at a rate of 5℃ / min and maintained at 135℃ for 10 minutes. The test is then stopped, and the lithium-ion batteries are checked for fire or explosion. The pass rate of the 135℃ hot chamber test = number of batteries that passed the 135℃ hot chamber test / total number of batteries tested at 135℃ (5 batteries).

[0074] Example 1-1

[0075] <Preparation of the first diaphragm>

[0076] A nonwoven fabric membrane with a thickness H1 of 12 μm and a glass transition temperature Tg1 of 90℃ was used as the first base membrane. The material of the nonwoven fabric membrane was polyethylene terephthalate, and the porosity P1 of the first base membrane was 55% (manufacturer: DuPont, grade: FR543).

[0077] The first adhesive is polyvinylidene fluoride (PVDF, Mw = 8.5 × 10⁻⁶). 6 ) and thickener sodium carboxymethyl cellulose (Mw = 8 × 10) 5 Mix them at a mass ratio of 98.5:1.5, add deionized water as a solvent, and stir evenly to form a first adhesive layer slurry with a solid content of 75wt%.

[0078] The first ceramic particles are alumina (Al2O3), and the first ceramic coating adhesive is styrene-butadiene rubber (Mw = 7 × 10⁻⁶). 6 Solvent and deionized water are mixed in a mass ratio of 35:10:55 to obtain the first ceramic coating slurry.

[0079] A first adhesive layer slurry is coated on one surface of a first base film and dried at 60°C to form a first adhesive layer on one surface of the first base film. A first ceramic coating slurry is coated on the other surface of the first base film and dried at 60°C to form a first ceramic coating on the other surface of the first base film. A first adhesive layer slurry is then coated on the surface of the first ceramic coating away from the first base film and dried to form another first adhesive layer on the surface of the first adhesive layer away from the first base film, thus obtaining the first diaphragm. The coating weight CW1 of the first adhesive layer is 0.0008 mg / mm². 2 The coating weight (CW3) of the first ceramic coating is 10 mg / cm³. 2 .

[0080] <Preparation of the Second Diaphragm>

[0081] A microporous membrane with a thickness H2 of 7 μm and a glass transition temperature Tg2 of 40 °C was used as the second base membrane. The microporous membrane was made of polypropylene and polyethylene, with a mass ratio of polypropylene to polyethylene of 1:1. The porosity P2 of the second base membrane was 18% (manufacturer: Celgard, grade: 2325).

[0082] The second adhesive, polyvinylidene fluoride (PVDF, Mw = 8.5 × 10⁻⁶), is used. 6 ) and the second thickener, sodium carboxymethyl cellulose (Mw = 8 × 10) 5 Mix the following materials at a mass ratio of 98.5:1.5, add deionized water as a solvent, and stir until homogeneous to form a second adhesive layer slurry with a solid content of 75wt%; then add the second ceramic particles alumina (Al2O3) and the second ceramic coating adhesive styrene-butadiene rubber (Mw = 7 × 10⁻⁶). 6 A second ceramic coating slurry is obtained by mixing solvent and deionized water in a mass ratio of 35:10:55. A second adhesive layer slurry is then coated onto one surface of the second base membrane and dried at 60°C to form a second adhesive layer on that surface. Similarly, a second ceramic coating slurry is coated onto the other surface of the second base membrane and dried at 60°C to form a second ceramic coating on that surface. Finally, a second adhesive layer slurry is coated onto the surface of the second ceramic coating furthest from the second base membrane and dried to form a second adhesive layer on that surface, thus obtaining the second diaphragm. The coating weight CW2 of the second adhesive layer is 0.0008 mg / mm². 2 The coating weight (CW4) of the second ceramic coating is 10 mg / cm³. 2 .

[0083] <Preparation of Negative Electrode Sheets>

[0084] Artificial graphite, styrene-butadiene rubber, and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 97.6:1.1:1.3, and deionized water was added as a solvent. After stirring evenly, a first negative electrode slurry with a solid content of 70 wt% was obtained. This first negative electrode slurry was also used as a second negative electrode slurry. The first negative electrode slurry was coated onto one surface of a 6 μm thick copper foil current collector and dried at 90°C to obtain a negative electrode sheet with a first negative electrode material layer coating thickness of 50 μm. The second negative electrode slurry was coated onto the other surface of the copper foil current collector and dried, resulting in a second negative electrode material layer coating thickness of 50 μm, and thus a negative electrode sheet with a total thickness of 106 μm. The coated negative electrode sheet was cold-pressed and then cut into 74 mm × 824 mm dimensions for later use. The compaction density of the first negative electrode material layer was 1.735 g / cm³. 3 The length is 720mm, and the compaction density of the second negative electrode material layer is 1.735g / cm³. 3 It is 680mm long.

[0085] <Preparation of the positive electrode>

[0086] Lithium cobalt oxide (CCO), conductive carbon black (CCO), and polyvinylidene fluoride (PVDF) (PVDF) were mixed in a mass ratio of 95:2.5:2.5. N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was thoroughly stirred to form a positive electrode slurry with a solid content of 75 wt%. This slurry was uniformly coated onto one surface of a 10 μm thick aluminum foil used as a positive electrode current collector and dried at 90°C to obtain a positive electrode sheet with a single-sided coating thickness of 55 μm. The positive electrode slurry was then coated onto the other surface of the aluminum foil, and after drying, the coating thickness on that surface was also 55 μm, resulting in a double-sided coated positive electrode sheet with a total thickness of 120 μm. The coated positive electrode sheets were then cold-pressed and cut into 70 mm × 800 mm dimensions for later use. The compaction density of the positive electrode material layer was 4.23 g / cm³. 3 .

[0087] <Preparation of Electrolyte>

[0088] In a glove box filled with a dry argon atmosphere, organic solvents propylene carbonate (PC), diethyl carbonate (DEC), and ethylene carbonate (EC) were mixed in a mass ratio of 1:1:1. Lithium hexafluorophosphate (LiPF6) was then added to the organic solvents, dissolved, and thoroughly mixed to obtain the electrolyte. The electrolyte contained 12% LiPF6 by mass, with the remainder being organic solvent.

[0089] <Preparation of Lithium-ion Batteries>

[0090] The prepared positive electrode, first separator, negative electrode, and second separator are stacked sequentially and then wound to obtain an electrode assembly. The positive electrode tab is spot-welded out using aluminum tabs, and the negative electrode tab is spot-welded out using nickel tabs. Specifically, the first ceramic coating in the first separator is close to the positive electrode, and the second ceramic coating in the second separator is away from the negative electrode. The first negative electrode material layer is close to the first separator, and the second negative electrode material layer is close to the second separator. The electrode assembly is placed in an aluminum-plastic film and dried in a vacuum oven at 80°C for 12 hours to remove moisture. Then, the prepared electrolyte is injected, and the lithium-ion battery is obtained after vacuum sealing, settling, formation (0.02C constant current charging to 3.5V, then 0.1C constant current charging to 3.9V), capacity testing, and shaping.

[0091] Examples 1-2 to Examples 1-7

[0092] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.

[0093] Examples 1-8

[0094] Except for the steps described below for preparing the lithium-ion battery, the rest is the same as in Example 1-1.

[0095] <Preparation of Lithium-ion Batteries>

[0096] The prepared positive electrode, first separator, negative electrode, and second separator are stacked sequentially and then wound to obtain the electrode assembly. The positive electrode tab is spot-welded with aluminum tabs, and the negative electrode tab is spot-welded with nickel tabs. Specifically, the first ceramic coating in the first separator is close to the positive electrode, and the second ceramic coating in the second separator is away from the negative electrode. The first negative electrode material layer is close to the second separator, and the second negative electrode material layer is close to the first separator. The electrode assembly is placed in an aluminum-plastic film and dried in a vacuum oven at 80°C for 12 hours to remove moisture. Then, the prepared electrolyte is injected. After vacuum sealing, settling, formation (0.02C constant current charging to 3.5V, then 0.1C constant current charging to 3.9V), capacity testing, and shaping processes, a lithium-ion battery is obtained.

[0097] Examples 2-1 to 2-12

[0098] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as in Examples 1-1. Specifically, when the coating weight CW1 of the first adhesive layer changes, the coating amount of the first adhesive layer slurry is adjusted so that CW1 is as shown in Table 2; when the coating weight CW2 of the second adhesive layer changes, the coating amount of the second adhesive layer slurry is adjusted so that CW2 is as shown in Table 2; when the coating weight CW3 of the first ceramic coating changes, the coating amount of the first ceramic coating slurry is adjusted so that CW3 is as shown in Table 2; when the coating weight CW4 of the second ceramic coating changes, the coating amount of the second ceramic coating slurry is adjusted so that CW4 is as shown in Table 2.

[0099] Comparative Example 1

[0100] Except for the fact that the preparation method of the first diaphragm is the same as that of the preparation method of the second diaphragm in Example 1-1, the rest is the same as in Example 1-1.

[0101] Comparative Example 2

[0102] Except for the preparation method of the second diaphragm, which is the same as the preparation method of the first diaphragm in Example 1-1, everything else is the same as in Example 1-1.

[0103] Comparative Examples 3 to 4

[0104] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.

[0105] The preparation and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.

[0106] Table 1

[0107]

[0108]

[0109] As can be seen from Examples 1-1 to 1-8 and Comparative Examples 1 to 4, setting a dual-membrane structure including a non-woven fabric membrane and a microporous membrane in the secondary battery, and adjusting the thickness of the non-woven fabric membrane and the microporous membrane within the scope of this application, reduces the thickness of the lithium-ion battery, indicating that the lithium-ion battery has a higher energy density in the same volume; it also improves the capacity retention rate and the pass rate of the hot box test at 130°C and 135°C, indicating that the lithium-ion battery of this application has a longer cycle life and better safety performance while taking into account energy density. As can be seen from Examples 1-1 to 1-8 and Comparative Example 1, when both the first and second membranes are microporous membranes, although the thickness of the lithium-ion battery is lower, i.e., the energy density is higher, the capacity retention rate and the pass rate of the hot box test at 135°C are lower, resulting in a shorter cycle life and poorer safety performance of the lithium-ion battery. As can be seen from Examples 1-1 to 1-8 and Comparative Example 2, when both the first and second separators are made of non-woven fabric membranes, although the pass rate of the hot box test at 130°C and 135°C is high, the cycle life is not significantly improved, and the thickness of the lithium-ion membrane is large, i.e., the energy density is low. The resulting lithium-ion battery, while having good safety performance, cannot simultaneously achieve high energy density. This demonstrates that the lithium-ion battery of this application achieves both high energy density and longer cycle life with better safety performance. In Comparative Example 3, the thickness of the non-woven fabric membrane is lower than the minimum value within the scope of this application. Although the lithium-ion battery has a lower thickness, i.e., higher energy density, the excessively low thickness allows lithium dendrites generated during cycling to pierce the low-strength microporous membrane, causing short circuits. This results in lower capacity retention and lower pass rates in the hot box test at 130°C and 135°C, leading to a shorter cycle life and poorer safety performance in the resulting lithium-ion battery. The thickness of the nonwoven membrane and microporous membrane in Comparative Example 4 is higher than the maximum value in the scope of this application. Although the pass rate of the hot box test at 130°C and 135°C of the lithium-ion battery is high, the excessive thickness of the nonwoven membrane and microporous membrane leads to an excessively long lithium-ion transport path, resulting in poor dynamic performance and shortened cycle life of the lithium-ion battery. In addition, the large thickness of the lithium-ion membrane means a lower energy density. The resulting lithium-ion battery has good safety performance, but it cannot achieve both good cycle performance and high energy density.

[0110] The materials of the first base film and / or the second base film typically affect the energy density, cycle life, and safety performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-5, when the materials of the first base film and / or the second base film are within the scope of this application, the lithium-ion battery thickness is smaller, i.e., the energy density is higher, and the capacity retention rate of the lithium-ion battery and the pass rate of the hot box test at 130°C and 135°C are higher. The lithium-ion battery of this application has a longer cycle life and good safety performance while taking into account the energy density.

[0111] The structure of the electrode assembly typically affects the energy density, cycle life, and safety performance of lithium-ion batteries. As can be seen from Examples 1-1 and 1-8, when the structure of the electrode assembly is within the scope of this application, the lithium-ion battery has a smaller thickness, i.e., a higher energy density, and the lithium-ion battery has a higher capacity retention rate and a higher pass rate in hot box tests at 130°C and 135°C. The lithium-ion battery of this application has a longer cycle life and better safety performance while taking into account energy density.

[0112] The glass transition temperature of nonwoven membranes and / or microporous membranes typically affects the energy density, cycle life, and safety performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-5, when the glass transition temperature of the nonwoven membrane and / or the glass transition temperature of the microporous membrane are within the range of this application, the lithium-ion battery thickness is smaller, i.e., the energy density is higher, and the capacity retention rate and the pass rate of the hot box test at 130°C and 135°C are higher. The lithium-ion battery of this application has a long cycle life and good safety performance while taking into account energy density.

[0113] Table 2

[0114]

[0115]

[0116] The coating weight of the first adhesive layer and / or the coating weight of the second adhesive layer typically affect the energy density, cycle life, and safety performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-1 to 2-4, when the coating weight of the first adhesive layer and / or the coating weight of the second adhesive layer are within the range of this application, the lithium-ion battery thickness is smaller, resulting in higher energy density. Furthermore, the lithium-ion battery capacity retention rate and the pass rate of the hot box test at 130°C and 135°C are also higher. The lithium-ion battery of this application achieves a long cycle life and good safety performance while maintaining energy density. However, in the lithium-ion battery of Examples 2-3, the coating weight of the first adhesive layer and the coating weight of the second adhesive layer are smaller, leading to poorer adhesion between the first separator and the positive electrode, the first separator and the negative electrode, the second separator and the positive electrode, and the second separator and the negative electrode. This results in a lower pass rate of the hot box test at 130°C and 135°C, and a decrease in the safety performance of the lithium-ion battery. In the lithium-ion batteries of Examples 2-4, the coating weight of the first adhesive layer and the coating weight of the second adhesive layer are relatively large, which may cause more pores in the first and second separators to be blocked, resulting in a low capacity retention rate and a decrease in the cycle performance of the lithium-ion battery.

[0117] The coating weight of the first ceramic coating and / or the coating weight of the second ceramic coating typically affect the energy density, cycle life, and safety performance of lithium-ion batteries. As can be seen from Examples 1-1, 2-5 to 2-8, when the coating weight of the first ceramic coating and / or the coating weight of the second ceramic coating are within the range of this application, the lithium-ion battery thickness is smaller, i.e., the energy density is higher, and the capacity retention rate of the lithium-ion battery and the pass rate of the hot box test at 130°C and 135°C are higher. The lithium-ion battery of this application has a longer cycle life and good safety performance while taking into account the energy density. During the hot box test, the first and second separators shrank. Because the coating weights of the first and second ceramic coatings in the lithium-ion batteries of Examples 2-7 were relatively small, the binding capacity of both the first and second ceramic coatings on the first and second separators was poor. This resulted in a low pass rate for the hot box tests at 130°C and 135°C, leading to a decrease in the safety performance of the lithium-ion batteries. Furthermore, the lower coating weights of the first and second ceramic coatings resulted in less electrolyte stored in both separators, leading to a decrease in the cycle performance of the lithium-ion batteries. In the lithium-ion batteries of Examples 2-8, the coating weights of the first and second ceramic coatings were relatively large, affecting the insertion and extraction of lithium ions and causing a decrease in the cycle performance of the lithium-ion batteries. Additionally, the thicker lithium ion layer affected the energy density of the lithium ions.

[0118] The porosity of the first base film and / or the second base film typically affects the energy density, cycle life, and safety performance of lithium-ion batteries. As seen in Examples 1-1, 2-9 to 2-12, when the porosity of the first base film and / or the second base film is within the range specified in this application, the lithium-ion battery thickness is smaller, resulting in higher energy density. Furthermore, the lithium-ion battery exhibits higher capacity retention and a higher pass rate in hot box tests at 130°C and 135°C. The lithium-ion battery of this application balances energy density with a longer cycle life and better safety performance. However, in Examples 2-12, the larger porosity of the first and second base films leads to lower strength of both films and a lower pass rate in hot box tests at 130°C and 135°C, resulting in decreased safety performance of the lithium-ion battery.

[0119] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.

[0120] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.

[0121] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A secondary battery comprising an electrode assembly, the electrode assembly including a positive electrode, a negative electrode, a first separator, and a second separator, the first separator being located between the positive electrode and the negative electrode, the negative electrode being located between the first separator and the second separator, the first separator including a first base membrane, the second separator including a second base membrane, the first base membrane being a non-woven fabric membrane, the second base membrane being a microporous membrane, the thickness of the non-woven fabric membrane being 10 μm to 15 μm, and the thickness of the microporous membrane being 5 μm to 9 μm; The electrode assembly is a wound structure. The negative electrode sheet includes a negative current collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative current collector. Along the winding direction of the electrode assembly, the length of the first negative electrode material layer is greater than the length of the second negative electrode material layer. The first separator is located on one side of the first negative electrode material layer of the negative electrode sheet, and the second separator is located on one side of the second negative electrode material layer of the negative electrode sheet.

2. The secondary battery according to claim 1, wherein, The first separator includes a first adhesive layer located on both sides of the first base film and a first ceramic coating disposed on the surface of the first base film near the positive electrode sheet, wherein the first ceramic coating is located between the first base film and the first adhesive layer; the second separator includes a second adhesive layer located on both sides of the second base film and a second ceramic coating disposed on the surface of the second base film away from the negative electrode sheet, wherein the second ceramic coating is located between the second base film and the second adhesive layer, wherein the coating weight of the first adhesive layer is greater than the coating weight of the second adhesive layer.

3. The secondary battery according to claim 2, wherein, The coating weight of the first adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 The coating weight of the second adhesive layer is 0.0004 mg / mm². 2 Up to 0.002 mg / mm 2 .

4. The secondary battery according to claim 2, wherein, The coating weight of the first ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2 The coating weight of the second ceramic coating is 7 mg / cm³. 2 Up to 13 mg / cm 2 .

5. The secondary battery according to claim 2, wherein, The first adhesive layer includes a first adhesive, and the second adhesive layer includes a second adhesive, wherein the first adhesive and the second adhesive are each independently selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethylene oxide, or polyimide.

6. The secondary battery according to claim 1, wherein, The porosity of the first base film is 40% to 70%, and the porosity of the second base film is 5% to 50%.

7. The secondary battery according to claim 1, wherein, The material of the first base film includes at least one of polyimide, polyamide, polysulfone, polyacrylonitrile, polyester, cellulose, polyetheretherketone, polyphenylene sulfide, polyacrylate, polyethylene terephthalate, poly(p-phenyleneamide), polyarylether sulfone ketone, aramid, or aramid sulfone. The material of the second base film includes polyolefin, and the polymerizing monomer of the polyolefin includes at least one of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-pentene, cyclobutene, cyclopentene, or cyclohexene.

8. The secondary battery according to claim 7, wherein, The nonwoven membrane is made of polyethylene terephthalate, and the microporous membrane is made of at least one of polypropylene and polyethylene.

9. The secondary battery according to claim 1, wherein, The glass transition temperature of the nonwoven membrane is 80°C to 100°C, and the glass transition temperature of the microporous membrane is 25°C to 50°C.

10. An electronic device comprising a secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2004171999A

  • A stack / folding type electrode assembly with safety improvement and a electrochemical cell comprising the same

    KR1020160015769A